Phase-separation: a possible new layer for transcriptional regulation by glucocorticoid receptor - Pinheiro, Ester da Silva; Preato, André Maciel; Petrucci, Tamirez Villas Boas; dos Santos, Lucas Souza; Glezer, Isaias (Frontiers in Endocrinology, 2023)
Glucocorticoids (GCs) are hormones involved in circadian adaptation and stress response, and it is also noteworthy that these steroidal molecules present potent anti-inflammatory action through GC receptors (GR). Upon ligand-mediated activation, GR translocates to the nucleus, and regulates gene expression related to metabolism, acute-phase response and innate immune response. GR field of research has evolved considerably in the last decades, providing varied mechanisms that contributed to the understanding of transcriptional regulation and also impacted drug design for treating inflammatory diseases. Liquid-liquid phase separation (LLPS) in cellular processes represents a recent topic in biology that conceptualizes membraneless organelles and microenvironments that promote, or inhibit, chemical reactions and interactions of protein or nucleic acids. The formation of these molecular condensates has been implicated in gene expression control, and recent evidence shows that GR and other steroid receptors can nucleate phase separation (PS). Here we briefly review the varied mechanisms of transcriptional control by GR, which are largely studied in the context of inflammation, and further present how PS can be involved in the control of gene expression. Lastly, we consider how the reported advances on LLPS during transcription control, specially for steroid hormone receptors, could impact the different modalities of GR action on gene expression, adding a new plausible molecular event in glucocorticoid signal transduction.